Future of the forest : struggles over land and law in India - Vaidya, Anand P., 1982- (Cornell Series on Land: New Perspectives on Territory, Development, and Environment Series., 2025)
"Future of the Forest is a historical and ethnographic account of the life of India's 2006 Forest Rights Act. The book follows the law from the movements that pushed for its passage to a North Indian forest village, showing how the law's meaning was shaped through ongoing collective action"--